Studies in the pure theory of international trade - Batra, Raveendra N. (New York : St. Martin's Press, 1973)
This is a textbook in pure international trade theory for the graduate or advanced undergraduate student. It includes several subtopics of trade theory: gains from trade, nominal tariffs, effective protection, economic expansion, intermediate products, factor market imperfections, product market imperfections, non-traded goods, investment, and growth. It uses mathematics like differential calculus and some simple linear algebra that is not be beyond the advanced undergraduate.
Includes bibliographies and index.
lje 22/1/19
Loans
Keywords: International trade; International economic relations